2014
DOI: 10.1371/journal.pone.0107912
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Bad and Looking Worse: Negative Affect Is Associated with Reduced Perceptions of Face-Healthiness

Abstract: Some people perceive themselves to look more, or less attractive than they are in reality. We investigated the role of emotions in enhancement and derogation effects; specifically, whether the propensity to experience positive and negative emotions affects how healthy we perceive our own face to look and how we judge ourselves against others. A psychophysical method was used to measure healthiness of self-image and social comparisons of healthiness. Participants who self-reported high positive (N = 20) or nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
3
19
1
Order By: Relevance
“…In Mirams et al's (2014) study, participants also completed a version of the face health judgement task in which they judged how they felt compared to healthy and unhealthy looking versions of a stranger, who was matched in age, gender and initial facial redness (i.e., 'how do I feel compared to this version of a stranger's face?'). Participants who self-reported high levels of NA judged themselves as equivalent to less healthy looking versions of a stranger's face and high self-esteem was associated with more favourable social comparisons of health (Mirams et al, 2014). This finding is in line with previous evidence suggesting that mood might affect social comparisons (for a review see Wheeler & Miyake, 1992).…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…In Mirams et al's (2014) study, participants also completed a version of the face health judgement task in which they judged how they felt compared to healthy and unhealthy looking versions of a stranger, who was matched in age, gender and initial facial redness (i.e., 'how do I feel compared to this version of a stranger's face?'). Participants who self-reported high levels of NA judged themselves as equivalent to less healthy looking versions of a stranger's face and high self-esteem was associated with more favourable social comparisons of health (Mirams et al, 2014). This finding is in line with previous evidence suggesting that mood might affect social comparisons (for a review see Wheeler & Miyake, 1992).…”
Section: Introductionsupporting
confidence: 86%
“…For example , Epley and Whitchurch (2008) found that healthy people, particularly those with high self-esteem, perceive themselves to look more attractive than they do in reality. Mirams et al (2014) also found that people can be biased in their perceptions of self-healthiness; compared to happy participants, those with dispositional tendencies to experience negative moods judged themselves as equivalent to less healthy looking versions of their own and another person's face. The purpose of the current study was to investigate whether experimentally induced, transient mood also moderates face health judgement and whether performing mood congruent social comparisons exacerbates the effect of mood on self-evaluations of healthiness.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations